Implementation of Academic Supervision to Improve Teachers' Ability to Integrate Learning Technology - Martina Sri Indriyati; Welius Purbonuswanto; Rahmat Mulyono (CV. Edujavare Publishing, 2026)
The integration of technology in education is no longer considered an optional innovation but has become a fundamental requirement for effective teaching and learning. This study aims to analyze the implementation of academic supervision and its impact on improving teachers’ ability to integrate learning technology at SDN Jolontoro. This research employed a qualitative case study design involving the school principal and teachers as research participants. Data were collected through observations, semi-structured interviews, and document analysis, including supervision programs, supervision reports, and technology-based lesson plans. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña, which consists of data condensation, data display, and conclusion drawing. The findings reveal that academic supervision at SDN Jolontoro was implemented systematically through planning, classroom observation, feedback, mentoring, and follow-up activities. The supervision process provided professional guidance that helped teachers improve their technological pedagogical competencies and effectively integrate digital learning tools into classroom instruction. Furthermore, academic supervision positively influenced teachers’ confidence, reflective practice, collaboration, and willingness to adopt innovative teaching strategies. As a result, teachers became more capable of utilizing technology to support student-centered learning and enhance classroom engagement. The study concludes that academic supervision plays a significant role in strengthening teacher professionalism and facilitating successful technology integration in elementary education.